ANALYSIS OF THE EFFECT OF REGIONAL ORIGINAL INCOME (PAD) ON ECONOMIC GROWTH IN TOJO UNA-UNA REGENCY IN 2010-2018 - Sri Rahayu Husen; Suwardi Zakaria; Amir Buhang (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aimed to find out the influence of regional original income (PAD) on economic growth in Tojo Una-Una district in 2010-2018. This study is a quantitative study. This study uses secondary data obtained from existing sources, namely in the form of documents at the Tojo Una-Una district of the Central Bureau of Statistics (BPS). The data was analyzed by quantitative analysis procedures to process numerical data so that it may be formed using statistical formulas. The findings revealed that calculations utilizing non-linear regression analysis provide the equation LnY = 1,006 + 0,42LnX. This demonstrates that Regional Original Income (X) positively influences Economic Growth (Y). This is demonstrated by the regression coefficient X, which is equal to 0,42. The calculation of the correlation coefficient (R) reveals that the correlation between the Regional Original Income variable (X) and the Economic Growth Variable (Y) is in the very strong category, with a value of 0,831. In addition, the coefficient of determination reveals that the regional original income variable (X) has a 69,1% effect on economic growth, while remaining 30% is affected by other variables beyond this study. According to the hypothesis test, the Tstatistic value was 3,957 whereas the Ttable value was 1,89457. In other words, there is a partial significant influence between the variables of Regional Original Income (X) on Economic Growth (Y) in Tojo Una-Una district in 2010-2018 period.